Potensi Keuntungan Private Label serta Proses Pemilihan Produk dan Pemasoknya pada Bisnis Ritel - Benny B. Tjandrasa (Jurnal Manajemen Maranatha, 2006)
The demand of products with private label will be likely to get higher as the consumers become more and more selective in buying the products of high quality with an optimal price. Considering this, retailers need to pay more attention to products with private label in facing the competition (especially with other retailers) which is getting tighter. The strong points of products with private label, low price and attractive packaging, need to be balance with the good quality of the products and the right choice of suppliers.